2020
DOI: 10.1111/jcmm.14925
|View full text |Cite
|
Sign up to set email alerts
|

circRNA circ‐CCND1 promotes the proliferation of laryngeal squamous cell carcinoma through elevating CCND1 expression via interacting with HuR and miR‐646

Abstract: Cyclin D1 (CCND1) is a well‐known proliferation promoter that accelerates G1/S transition in cancer. However, the underlying mechanism by which CCND1 is regulated is still largely unknown. In this study, we identified a novel circular RNA (circRNA) derived from CCND1 (circ‐CCND1, hsa_circ_0023303) as a key regulator for CCND1. circ‐CCND1 was found to be markedly up‐regulated in laryngeal squamous cell carcinoma (LSCC) and closely associated with aggressive clinical features and adverse prognosis. Depletion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 28 publications
3
41
0
Order By: Relevance
“…A recent study in 2020 collected 76 matched LSCC and normal tissues (101 cases in total) to assess the circ-CCND1 expression. The results showed that circ-CCND1 was markedly up-regulated in LSCC tissues compared to the precancerous tissues (3). In a study on the expression of immunohistochemical markers in non-oropharyngeal HNSCC in Ghana, the commonest primary site was the larynx 41.3% with 4.7% positivity for CD1 expression (14).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A recent study in 2020 collected 76 matched LSCC and normal tissues (101 cases in total) to assess the circ-CCND1 expression. The results showed that circ-CCND1 was markedly up-regulated in LSCC tissues compared to the precancerous tissues (3). In a study on the expression of immunohistochemical markers in non-oropharyngeal HNSCC in Ghana, the commonest primary site was the larynx 41.3% with 4.7% positivity for CD1 expression (14).…”
Section: Resultsmentioning
confidence: 98%
“…Laryngeal squamous cell carcinoma (LSCC) accounts for roughly 90% of all malignant tumors of the larynx and is the second most prevalent malignancy of the respiratory system ( 1 , 2 ). In recent decades, the total number of patients that are diagnosed with LSCC has increased drastically leading to as low as 5 years or less in the survival rate of LSCC patients especially in advanced stages ( 3 ). Some of the early symptoms of LSCC are hoarseness, dysphagia and cervical lymph node metastasis ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences showed that circRNA functioned as miRNA sponge to promote the activity of mRNA [19][20][21]. Recently, researchers have focused on circRNA-miRNA-mRNA, as a novel regulatory mechanism of competing endogenous RNA (ceRNA), aiming at understanding RNA interactions deeply [22].…”
Section: Introductionmentioning
confidence: 99%
“…Circ_0067934 was upregulated in LSCC tissues and its overexpression was associated with larger tumor size, stronger lymph node metastasis, distant metastasis, and poor prognosis with lower OS rate (Chu, 2020). Upregulated circ-CCND1 levels in LSCC correlated with tumor size, poor differentiation, advanced TNM stage, and poor prognosis (Zang et al, 2020). It binds to HuR and miR-646 to enhance the stability of CCND1 mRNA (Zang et al, 2020).…”
Section: Laryngeal Squamous Cell Carcinoma (Lscc)mentioning
confidence: 99%
“…Upregulated circ-CCND1 levels in LSCC correlated with tumor size, poor differentiation, advanced TNM stage, and poor prognosis (Zang et al, 2020). It binds to HuR and miR-646 to enhance the stability of CCND1 mRNA (Zang et al, 2020). CircFLNA upregulation in LSCC was associated with lymph node metastasis (Wang J. X. et al, 2019).…”
Section: Laryngeal Squamous Cell Carcinoma (Lscc)mentioning
confidence: 99%